Discovery of hydrogen spillover-based binary electrocatalysts for hydrogen evolution: from theory to experiment - Tan, Yuan (2023)
Hydrogen spillover-based binary (HSBB) catalysts have attracted more and more attention in recent years because of their unique reaction mechanism, different from traditional single-component catalysts. In this paper, using density functional theory for the screening of materials, we find 11 candidates with excellent hydrogen evolution reaction (HER) performance under acidic conditions. Among them, Pt1Ir1-MoS2has been successfully synthesized and verified through experiment to have exhibited the outstanding catalytic performance as predicted. Detailed analysis of these HSBB catalysts reveals the key role of hydrogen spillover toward efficient water splitting, paving the way for the discovery of widely applicable materials and a feedback loop that delivers materials as designed. Greatly increasing the number of known HSBB catalysts, the current study not only demonstrates the accuracy of our screening of materials but also provides a novel paradigm for accelerating the development of materials and reducing costs.